2004
DOI: 10.2133/dmpk.19.48
|View full text |Cite
|
Sign up to set email alerts
|

Transepithelial Permeation of Tolbutamide across the Human Intestinal Cell Line, Caco-2

Abstract: Sulfonylurea hypoglycemic agents have interindividual variability in the gastrointestinal absorption rate. However, the absorption mechanism at the intestinal epithelium has not yet been clarified. To elucidate contribution of the specific mechanism for transepithelial transport of sulfonylureas, the apical-to-basolateral and basolateral-to-apical transport studies of tolbutamide were carried out using Caco-2 cell monolayers cultured on the polycarbonate membrane. The transported amounts of the substrate were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…2). The respiration inhibitor ofazide (at 10 mM) is found to inhibit thisfucoidantransport; i.e., this inhibition of transport is found to be significant(p < 0.05; Mann-Whitney's U test; two-tailed test).Similar observation of 77% inhibition (p < 0.001; n = 3~4) by azide (10 mM) onto the transport of a small molecule of tolbutamide (a sulphonylurea drug for type II diabetes; Mr 270.4) in Caco-2 cells has been reported by Nishimura et al [9].…”
Section: Statisticssupporting
confidence: 84%
See 2 more Smart Citations
“…2). The respiration inhibitor ofazide (at 10 mM) is found to inhibit thisfucoidantransport; i.e., this inhibition of transport is found to be significant(p < 0.05; Mann-Whitney's U test; two-tailed test).Similar observation of 77% inhibition (p < 0.001; n = 3~4) by azide (10 mM) onto the transport of a small molecule of tolbutamide (a sulphonylurea drug for type II diabetes; Mr 270.4) in Caco-2 cells has been reported by Nishimura et al [9].…”
Section: Statisticssupporting
confidence: 84%
“…5. FCCP inhibits the fucoidan transport by 33% (significance p< 0.05; Mann-Whitney's U test; one-tailed test), but ClCCPdoes not (about 13% inhibition, but not significant).Nishimura et al alsohave reported the observation of 12% inhibition (p < 0.05; n = 3~4) by FCCP (0.05mM) onto the transport oftolbutamide in Caco-2 cells [9].The inhibition on the fucoidan transport byClCCPhas not reached to the significant level on the contrary to theprevious observation in the bacterial artificial membrane vesicles [10]. Thisdiscrepancy may be due to the chemical differences in the membranes between bacterial cells and human colon cancer cells.Since this fucoidan transport demonstrated byCaco-2 cells monolayeris inhibited by both the respiration inhibitor of azide and theuncoupler of FCCP, thetype of fucoidan transport by Caco-2 cells is considered to be a typical energy-requiringactive-transport.…”
Section: Statisticsmentioning
confidence: 94%
See 1 more Smart Citation
“…Because pomegranate juice is an inhibitor of CYP3A (Hidaka et al, 2005), the juice may be also an inhibitor of P-glycoprotein in the intestine and enhance the absorption of drugs. However, Nishimura et al (2004) reported that basolateralto-apical transport of tolbutamide across the Caco-2 cell monolayers was not operated by the carrier-mediated transport system including P-gp efflux. Therefore, the inhibition of P-glycoprotein by pomegranate juice likely would not be associated with the increased bioavailability of tolbutamide.…”
Section: Controlmentioning
confidence: 99%
“…However, the visualization of the cellular transport process occurring on Transwell system in real-time and in situ has not been realized yet. Up to now, the main method used to verify the transported substance using Transwell system is to sample the basolateral medium at predetermined time points and quantify the transported substance by HPLC 16) or other quantitative instruments. 17,18) In the studies of interaction with cells, fluorescent reagents are often used include Coumarin 6 (C6) 19) etc.…”
mentioning
confidence: 99%